ANALYSIS OF FLOUTING MAXIMS AND CONVERSATIONAL IMPLICATURE TRANSLATION STRATEGIES IN ONE PIECE (LIVE-ACTION SERIES 2023) SUBTITLE - Roselin Ahmadi; Farizka Humolungo; Fanny Puji Rakhmi (Politeknik Negeri Jakarta, 2024)
This study examines the flouting of Cooperative Principle maxims in conversational implicature and Gottlieb’s translation strategies used in the subtitles of One Piece (Live-Action Series 2023). This study aims to identify which conversational maxims are flouted, Gottlieb’s translation strategies employed, and how these implicatures are translated into the target language. This study used a qualitative descriptive method with document analysis as the data collection technique. The results showed that all four conversational maxims were flouted, and some implicatures flouted multiple maxims simultaneously. Most implicatures were translated into the same implicature in the target text, while a small number were translated explicitly and have undergone explicitation. The most frequently used translation strategy was Paraphrase, followed by Condensation, Transfer, Dislocation, Decimation, Expansion, and Deletion. Most of the implicatures translated explicitly use the Paraphrase strategy to ensure that the utterances are clear and align with the conversation.